2006
DOI: 10.1093/brain/awl203
|View full text |Cite
|
Sign up to set email alerts
|

APP duplication is sufficient to cause early onset Alzheimer's dementia with cerebral amyloid angiopathy

Abstract: We assessed the impact of amyloid precursor protein (APP) gene locus duplications in early onset Alzheimer's disease in a Dutch population-based sample. Using real-time PCR and an in-house-developed multiplex amplicon quantification assay, we identified a genomic APP duplication in 1 out of 10 multigenerational families segregating early onset Alzheimer's disease. In this family, cerebral amyloid angiopathy (CAA) coincided with this disease. The duplicated genomic region included no other genes than APP and ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
255
2
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 339 publications
(275 citation statements)
references
References 25 publications
11
255
2
1
Order By: Relevance
“…[12][13][14] The association between SMN1 gene copy number and ALS previously found in French and Dutch population corroborated this hypothesis in MND. [2][3][4] As almost all genetic association studies led to controversial results, we aimed to strengthen the findings of an association between SMN1 copy number and SALS in a third unrelated population.…”
Section: Discussionsupporting
confidence: 58%
“…[12][13][14] The association between SMN1 gene copy number and ALS previously found in French and Dutch population corroborated this hypothesis in MND. [2][3][4] As almost all genetic association studies led to controversial results, we aimed to strengthen the findings of an association between SMN1 copy number and SALS in a third unrelated population.…”
Section: Discussionsupporting
confidence: 58%
“…Primers from within the APP promoter, APP5e (exon 5) and APP18i (the intron after exon 18) were used in Sleegers et al 9 Primers for the control genes hemoglobin beta (HBB) on chromosome 11, glyceraldehyde-3-phosphate dehydrogenase (GAPDH) on chromosome 12 and ubiquitin C (UBC) on chromosome 12, have previously been used in Johnson et al, 14 West et al 15 and in Sleegers et al, 9 respectively.…”
Section: Allele Quantificationmentioning
confidence: 99%
“…7 Also, two research groups have recently reported that duplications of APP, in the absence of trisomy 21, can cause familial EOAD with cerebral amyloid angiopathy (EOAD/CAA). 8,9 In this study, we screened for APP duplications in affected subjects from Swedish and Finnish families and cases with EOAD in an effort to estimate the frequency of APP duplications in EOAD patients in these populations.…”
Section: Introductionmentioning
confidence: 99%
“…11,13,109 , but currently there are insufficient data on these phenotypes to compare Dup-APP with AD-DS or LOAD. As in AD-DS, there is a greatly increased risk of dementiaassociated seizures in Dup-APP [10][11][12][13]47 , in contrast to LOAD, in which seizures are relatively rare. This suggests that duplication of APP, and possibly of other genes located nearby, could be epileptogenic; however, as late-onset seizures often follow onset of dementia, they may also be related to synaptic deterioration that results in abnormal synchronization of neuronal networks and hyperexcitability 110 .…”
mentioning
confidence: 99%